NSAID-INDUCED GASTROPATHIES IN CHILDREN WITH RHEUMATIC DISEASES: DIAGNOSTICS AND TREATMENT - P I Nikishina; N N Kuzmina; A E Karateyev (Научно-практическая ревматология)
168 patients aged 4-15 years were endoscopically examined aiming at the study of prevalence and structure of NSAID - gustropathy in children with rheumatic diseases. Serious injury of mucous of upper gastrointestinal tract (erosions and ulcers) were found in 21% of children with prevalent localization in the region of the bulb of duodenum and in 50% ofpatients surface changes were revealed. In the group under study there were no reliable dependence between the degree of subjective and objective symptoms of NSAID - gustropathy and no associations of peculiarities of endoscopic changes with the character and duration of medicamentong therapy. The experience of Famotidin using ( Famosan, Pro.Med.CS. Praha c.s.) in 40 children with most pronounced manifestations of drug-induced gastroduodenopathies demonstrated its high efficacy, manifested in quick ceasing of complaints in all patients, healing of erosions and ulcers in great majority of patients with absence of side-ejfects.